Cobalt sulfides constructed heterogeneous interfaces decorated on N, S-codoped carbon nanosheets as a highly efficient bifunctional oxygen electrocatalyst. Issue 24 (11th June 2021) - Sun, Changbin; Ding, Jia; Wang, Haozhi; Liu, Jie; Han, Xiaopeng; Deng, Yida; Zhong, Cheng; Hu, Wenbin
Abstract : The Co9 S8 /Co1− x S@NSC heterostructures have been prepared by a one-pot salt template-assisted pyrolysis procedure, which exhibit superior bifunctional oxygen electrocatalysis and zinc–air battery performances. Abstract : The rational design and controllable synthesis of excellent bifunctional oxygen reduction and evolution reaction (ORR/OER) electrocatalysts are of vital importance for zinc–air battery applications. Herein, we report nitrogen/sulfur-codoped carbon nanosheets (NSC) decorated with dense Co9 S8 /Co1− x S heterostructures (Co9 S8 /Co1− x S@NSC), prepared by a one-pot salt template-assisted pyrolysis procedure. The population of the Co9 S8 /Co1− x S heterostructure can be effectively controlled by tuning the precursor components. Salt templates constructed hierarchical porosity for the wide-open carbon nanosheets, which maximized the N functional groups to anchor highly dispersive Co9 S8 /Co1− x S species. Experiments and theoretical simulations revealed notable electronic interactions within Co9 S8 /Co1− x S interfaces, which can effectively optimize the adsorption/desorption behaviors of intermediates in ORR/OER, thus promoting the bifunctional electrocatalytic performance. The half-wave potential for the ORR of 0.86 V and the OER electrocatalytic potential of 1.52 V at 10 mA cm −2 were obtained. Benefiting from the strong coupling effect between the Co9 S8 /Co1− x S species and the carbon substrate, superior durability was obtained for 2000 ORR/OER cycles. The practical zinc–air battery based on the Co9 S8 /Co1− x S@NSC cathode manifested a high open-circuit voltage, small voltage gap and robust reversibility. Our study revealed the great potential of the bi-elemental (Co and S) heterostructure in enhancing the ORR/OER activity, which suggests a logical extension to other electrocatalysis systems.